Monomer material containing benzisoxazole structure, conjugated polymer composite material, preparation method and application
By using monomer materials and conjugated polymer composite materials containing benziisoxazole structure, the problem of poor performance of plastics in high-temperature environments is solved, the heat resistance temperature and mechanical properties of plastics are improved, and solar energy is improved Battery performance.
Patent Information
- Application Number
- CN202411344302.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-02-18
AI Technical Summary
In the plastic industry, the prior art is difficult to effectively improve the heat resistance temperature and mechanical properties of plastics, which limits its application in high-temperature environments.
Using monomer materials containing benziisoxazole structure and conjugated polymer composite materials, the fused ring structure of benziisoxazole is introduced into unit A as copolymerized polymer, and copolymerized with different units D to form a broadband. A conjugated polymer composite material with gap, medium band gap.
It significantly improves the heat resistance temperature and mechanical properties of plastics, improves the performance stability in high-temperature environments, and forms a highly ordered polymer film with high carrier migration characteristics through π-π supramolecular interaction, which improves the Filling factor and photocurrent of solar cells.
Smart Images

Figure CN119462636A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of plastics, and in particular relates to a monomer material containing a benzisoxazole structure, a conjugated polymer composite material, and a preparation method and application thereof. Background Art
[0002] The development of organic / polymer composite materials provides a new way to prepare low-cost, large-area optoelectronic devices. In the late 1970s, Alan J. Heeger and others invented conductive polymers, which completely overturned the traditional concept that organic materials based on carbon atoms are insulators and opened up the emerging scientific field of organic / polymer semiconductor electronics. Since then, the optical, electrical, and magnetic properties of organic materials have gradually begun to be recognized by humans, and various optoelectronic devices based on them have also attracted people's attention. Organic / polymer semiconductor composite materials not only have the electronic properties of metals or semiconductors, but are also much easier to process than metals or crystalline semiconductors. The possibility of processing electronic materials at low temperatures brings hope for cheap processing of electronic devices. More importantly, solution-processable organic / polymer semiconductor materials can be used as electronic "ink". Combining with traditional printing technology (inkjet printing, offset printing, etc.) will revolutionize the manufacture of electronic devices. At the same time, electronic devices based on organic / polymer semiconductor composite materials can also realize some applications that require special mechanical properties (such as flexible devices). Due to these special advantages, organic / polymer composite materials are very suitable for industrial production and promotion, and have broad commercial prospects.
[0003] Since the Tang Qingyun research group of Kodak in the United States proposed organic small molecule thin film electroluminescent devices in 1987 [Tang, CW; Van Slyke SA et.al; Appl. Phys. Lett. 1987, 51, 913.] and the RHFriend research group of Cambridge University in the United Kingdom proposed organic polymer thin film electroluminescent devices in 1990 [Burroughes, JH; Bradley, DDC; Friend, RH; Holmes, AB et.al; Nature 1990, 347, 539.], organic flat panel display technology has made great progress and has now entered the industrialization stage, becoming the next generation product to replace liquid crystal displays. At the same time, organic optoelectronic fields such as organic solar cells, organic field effect transistors, organic bio and chemical sensors have also achieved vigorous development. Especially in recent years, due to the increasing energy consumption and the demand for low-carbon and environmental protection, traditional energy sources such as coal, oil and natural gas have limited reserves and are polluting and emit greenhouse gases. Therefore, renewable clean energy represented by solar energy is increasingly valued by people, and organic solar thin-film batteries are very popular. In the past two years, the efficiency of organic thin-film batteries has repeatedly set new highs and is favored by the industry. The market prospects are very bright.
[0004] However, in the field of plastics industry, the demand for high-performance plastics is increasing. In order to improve the performance of plastics, researchers have begun to try to apply conjugated polymer composites with special properties to plastic modification to enhance the overall performance of plastics. Conjugated polymer composites containing benzisoxazole have been proven to have significant application advantages in the field of plastic modification due to their unique structure and properties. They can significantly increase the heat resistance temperature of plastics, thereby enhancing the performance stability in high temperature environments. In addition, they can also be combined with plastic matrices to improve the mechanical properties of materials.
[0005] In summary, materials containing benzisoxazole structures have broad application potential in the field of plastic modification. Further exploration of the application of materials containing benzisoxazole structures in plastic modification has important practical significance and research value. Summary of the invention
[0006] Therefore, the purpose of the present invention is to provide a monomer material containing a benzisoxazole structure and a conjugated polymer composite material, which combines the design principles of the currently common DA copolymer polymer donor, innovatively introduces a condensed ring structure containing benzisoxazole as the A unit therein, and the synthesized organic composite material has good performance.
[0007] The present invention discloses a monomer material containing a benzisoxazole structure, wherein the monomer material containing a benzisoxazole structure has the following structure:
[0008]
[0009] in,
[0010] The R is selected from alkyl derivatives;
[0011] Said A1 and A2 are independently selected from alkyl and alkyl derivatives;
[0012] The B1 and B2 are independently selected from oxygen atoms and nitrogen atoms, and the types of the selected B1 and B2 are different.
[0013] Further, all carbon atoms on the alkyl derivative are unsubstituted, or one or more carbon atoms are substituted by one or more of oxygen atoms, nitrogen atoms, phosphorus atoms, amino groups, sulfone groups, carbonyl groups, aryl groups, alkenyl groups, alkynyl groups, ester groups, cyano groups, and nitro groups;
[0014] All hydrogen atoms on the alkyl derivative are unsubstituted, or one or more hydrogen atoms are substituted by one or more of halogen, hydroxyl, amino, carboxyl, cyano, nitro, aryl, alkene, and alkyne.
[0015] The present invention also provides the following steps:
[0016] L1, adding halogenated benzaldehyde to fuming nitric acid, nitrifying reaction, purifying, to obtain compound 2;
[0017] L2, adding compound 2 to a solvent, adding a reducing agent under the protection of an inert gas, stirring to react, and purifying to obtain compound 3;
[0018] L3. Under the protection of an inert gas, compound 3, a tributyltinated thiophene unit containing an R group, and a catalyst are added to a solvent, heated for reaction, and purified to obtain compound 4;
[0019] L4, adding the compound 4 into a solvent, and then adding a halogenating agent, reacting, and purifying to obtain a monomer material containing a benzisoxazole structure.
[0020] Further, in step L1, multiple hydrogens in the halogenated benzaldehyde are replaced by halogens;
[0021] The halogen is selected from chlorine, bromine and iodine.
[0022] Furthermore, in step L2, the reducing agent is selected from one or more of stannous chloride, potassium borohydride, sodium borohydride, and lithium aluminum hydride.
[0023] The present invention also provides a conjugated polymer composite material containing benzisoxazole, wherein the conjugated polymer composite material containing benzisoxazole has the following structure:
[0024]
[0025] Wherein, n is a natural number greater than 1;
[0026] The C unit is an electron donating group.
[0027] Furthermore, the C unit is selected from one or more of the following structures:
[0028]
[0029]
[0030] Wherein, R1 and R2 are independently selected from one or more of alkyl groups and alkyl derivatives;
[0031] One or more carbon atoms on the alkyl derivative are substituted by one or more of oxygen atoms, amino groups, sulfone groups, carbonyl groups, aryl groups, alkenyl groups, alkynyl groups, ester groups, cyano groups, and nitro groups;
[0032] and / or
[0033] One or more hydrogen groups on the alkyl derivative are replaced by one or more of halogen, hydroxyl, amino, carboxyl, cyano, nitro, aryl, alkene, and alkyne.
[0034] Preferably, the C unit is selected from one or more of the following structures:
[0035]
[0036] The present invention also provides a method for preparing the conjugated polymer composite material containing benzisoxazole, comprising the following steps:
[0037] The monomer material containing benzisoxazole structure, coupling compound and catalyst are added into a solvent, heated for reaction under the protection of inert gas, and purified to obtain the conjugated polymer composite material containing benzisoxazole.
[0038] Furthermore, the catalyst is selected from palladium catalysts.
[0039] Furthermore, the halogenating agent is selected from N-bromosuccinimide.
[0040] Furthermore, the coupling compound is selected from one of a bis(trimethyltin) terminal compound and a bis(borate) terminal compound.
[0041] Specifically, the conjugated polymer composite material containing benzisoxazole is dissolved in an organic solvent, processed into a polymer film by spin coating, printing, roll-to-roll or inkjet printing solution, and used as a carrier transport layer, P-type material, light-emitting layer or photovoltaic active layer in photovoltaic, light-emitting or field effect transistor photoelectric devices.
[0042] The present invention also provides the use of the conjugated polymer composite material containing benzisoxazole in organic solar cells;
[0043] The organic solar cell comprises the following structures from bottom to top: a cathode, a cathode interface layer, a light absorption layer, an anode interface layer, and an anode;
[0044] Wherein, the material of the photovoltaic active layer is the conjugated polymer composite material containing benzisoxazole.
[0045] Furthermore, the cathode is selected from one or more of doped tin dioxide, zinc oxide, indium gallium zinc oxide or graphene and their derivatives.
[0046] Furthermore, the anode interface layer is selected from one or more of organic conjugated polymers or inorganic semiconductor materials.
[0047] The invention also provides application of the conjugated polymer composite material containing benzisoxazole in plastic modified materials.
[0048] Compared with the prior art, the main advantages of the present invention are as follows:
[0049] The monomer material and conjugated polymer composite material of the present invention have a benzisoxazole unit structure. Since benzisoxazole has a strong electron-withdrawing ability, it is suitable as the A unit in the DA copolymer donor. Copolymerization with different D units can respectively obtain conjugated polymer composite donors with wide band gap and medium band gap, so that the monomer material and conjugated polymer composite material of the present invention have a strong rigid conjugated plane, and can form a polymer film with high order and high carrier mobility characteristics through π-π supramolecular interaction, so as to ensure that it has good carrier mobility. This characteristic can not only improve the filling factor of the conjugated polymer composite solar cell, but also can match different acceptor materials to obtain a photovoltaic active layer with complementary light absorption, realize the effective absorption and utilization of sunlight, and improve photocurrent. In addition, since the conjugated polymer composite material containing benzisoxazole of the present invention has two electron-deficient units, the conjugated polymer composite material has a stronger electron-withdrawing ability, so as to ensure that the conjugated polymer composite material has lower HOMO and LUMO energy levels. It can be seen that the conjugated polymer composite material containing benzisoxazole has a wide range of application potential in the field of plastic modification. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 The nuclear magnetic resonance spectrum (1H NMR) of compound 2 synthesized in Example 1;
[0051] Figure 2 The nuclear magnetic resonance spectrum (1H NMR) of compound 3 synthesized in Example 1;
[0052] Figure 3 The nuclear magnetic resonance spectrum (1H NMR) of compound 4 synthesized in Example 1;
[0053] Figure 4 The nuclear magnetic resonance spectrum (1H NMR) of the M1 monomer synthesized in Example 1;
[0054] Figure 5 It is the UV-visible (UV) absorbance curve of LJQD-1 solid film, Y6 solid film and LJQD-1:Y6 mixed film;
[0055] Figure 6 is the chemical structure diagram of Y6;
[0056] Figure 7 The current-voltage curve of the organic solar cell device with LJQD-1 as electron donor and Y6 as electron acceptor under illumination conditions;
[0057] Figure 8This is a diagram of the structure of an organic solar cell device. DETAILED DESCRIPTION
[0058] In order to more clearly illustrate the technical solution of the present invention, the following examples are listed. Unless otherwise stated, the raw materials, reactions and post-treatment methods shown in the examples are common raw materials on the market and technical methods well known to those skilled in the art.
[0059] Tributyltin-substituted thiophene with EH alkyl chain was purchased from Jiangsu Jia Biotechnology Co., Ltd., CAS: 886746-54-9.
[0060] Example 1
[0061] Synthesis of M1 monomer
[0062] The monomer synthesis route is as follows:
[0063]
[0064] L1, Synthesis of 2,5-dibromo-6-nitrobenzaldehyde (Compound 2)
[0065] Under an ice bath, 6 ml of fuming nitric acid was dissolved in 30 mL of concentrated sulfuric acid, and 2.6 g of 2,5-dibromobenzaldehyde was added in batches. After reacting for 3 h, the mixture was poured into ice water, filtered, and dried to obtain 2.44 g of a white powdery solid. After purification by silica gel column chromatography (petroleum ether: dichloromethane = 5:1, v / v) to remove isomers, 1.5 g of compound 2 was obtained, with a yield of 48%;
[0066] The NMR data of the product are as follows: 1H NMR (600 MHz, Chloroform-d) δ 10.21 (s, 1H), 7.79–7.67 (m, 2H).
[0067] Figure 1 This is the nuclear magnetic resonance spectrum (1H NMR) of compound 2 synthesized in Example 1.
[0068] Synthesis of L2, 4,7-dibromobenzisoxazole (Compound 3)
[0069] 3 g of compound 2 was dissolved in 40 mL of a mixed solvent of ethyl acetate:methanol = 1:1 (v / v), and 13.5 g of anhydrous stannous chloride was added under nitrogen protection. The mixture was stirred at room temperature for 24 h. After the reaction, the reaction solution was neutralized with a saturated sodium bicarbonate aqueous solution, filtered, and the liquid phase was extracted with dichloromethane (100 ml × 3). The organic layer was washed with water and the organic phases were combined; after drying with magnesium sulfate, the solvent was evaporated under reduced pressure, and the mixture was purified by silica gel column chromatography (petroleum ether: dichloromethane = 5:1, v / v) to obtain 2.4 g of compound 3 with a yield of 88%;
[0070] The NMR data of the product are as follows: 1H NMR (600 MHz, Chloroform-d) δ 9.27 (s, 1H), 7.41 (d, J = 7.4 Hz, 1H), 7.08 (d, J = 7.3 Hz, 1H).
[0071] Figure 2 This is the nuclear magnetic resonance spectrum (1H NMR) of compound 3 synthesized in Example 1.
[0072] L3, Synthesis of 4,7-dithiophenebenzisoxazole (Compound 4) (Alkyl chain is 2-EH)
[0073] Under argon atmosphere, 1.5 g of compound 3, 7.8 g of tributyltin-substituted thiophene with an EH alkyl chain and 0.312 g of tetrakis(triphenylphosphine)palladium were added to a pressure bottle, 40 ml of toluene was added, the pressure bottle was sealed, and the mixture was stirred and reacted at 150° C. for 24 h. After the reaction was completed, the solvent was evaporated under reduced pressure and purified by silica gel column chromatography (petroleum ether: dichloromethane=10:1, v / v) to obtain 1.4 g of compound 4 with a yield of 53%;
[0074] The NMR data of the product are as follows: 1H NMR (600 MHz, Chloroform-d) δ9.49 (s, 1H), 7.92 (s, 1H), 7.56 (d, J = 7.2 Hz, 1H), 7.24 (d, J = 4.2 Hz, 2H), 6.97 (d, J = 17.0 Hz, 2H), 2.60 (dd, J = 6.7, 4.9 Hz, 4H), 1.36–1.29 (m, 16H), 0.94–0.88 (m, 14H).
[0075] Figure 3 This is the nuclear magnetic resonance spectrum (1H NMR) of compound 4 synthesized in Example 1.
[0076] L4, Synthesis of monomer material containing benzisoxazole structure (M1 monomer)
[0077] At room temperature, 0.44 g of compound 4 was dissolved in 5 ml of chloroform and kept away from light. 0.32 g of NBS was added in batches and stirred for reaction at room temperature for 30 min. After the reaction, deionized water was added to quench the reaction, and the mixture was extracted with dichloromethane. The solvent was evaporated under reduced pressure and purified by silica gel column chromatography (petroleum ether: dichloromethane = 10:1, v / v) to obtain 0.4 g of M1 monomer with a yield of 68%.
[0078] The NMR data of the product are as follows: 1H NMR (600 MHz, Chloroform-d) δ9.44 (s, 1H), 7.76 (s, 1H), 7.46 (d, J = 7.2 Hz, 1H), 7.16 (d, J = 7.2 Hz, 1H), 7.09 (s, 1H), 2.56 (dd, J = 7.2, 2.6 Hz, 4H), 1.37–1.28 (m, 16H), 0.97–0.85 (m, 14H).
[0079] Figure 4 This is the nuclear magnetic resonance spectrum (1H NMR) of the M1 monomer synthesized in Example 1.
[0080] Example 2
[0081] Synthesis of Conjugated Polymer Composites Containing Benzisoxazole (LJQD-1)
[0082] The synthetic route is as follows:
[0083]
[0084] Under argon protection, 0.1026 g of M1 monomer, 0.1449 g of BDT-F, 4.8 mg of bis(dibenzylideneacetone)palladium, and 7.2 mg of tri(o-methylphenyl)phosphine were added to a pressure bottle, dissolved with 10 ml of chlorobenzene, and the pressure bottle was sealed. After stirring at 80 ° C for 36 hours, the temperature was raised to 100 ° C and the stirring reaction was continued for 36 hours. After the reaction was completed, the reaction solution was dripped into methanol, and the obtained precipitate was extracted with methanol, n-hexane, dichloromethane and chloroform in sequence using a Soxhlet extractor. After removing the solvent from the chloroform phase, it was dripped into methanol and dried to obtain 125.5 mg of LJQD-1 with a yield of 70%.
[0085] Test Example 1
[0086] After LJQD-1 was prepared into thin films, its performance was tested to show that LJQD-1 can be used as a donor material for solar cells;
[0087] Preparation of LJQD-1 solid film: Take an appropriate amount of LJQD-1 material, completely dissolve it in chloroform to make a solution with a concentration of 7 mg / mL, and prepare a thin film on a quartz substrate by spin coating (single spin coating solution volume 15 μL, spin coating speed 3000 Rpm).
[0088] Preparation of Y6 solid film: Take an appropriate amount of Y6 material, completely dissolve it in chloroform to make a solution with a concentration of 10 mg / mL, and prepare a thin film on a quartz substrate by spin coating (single spin coating solution volume 15 μL, spin coating speed 3000 Rpm).
[0089] Preparation of LJQD-1:Y6 mixed film: Take appropriate amount of LJQD-1 and Y6 materials, completely dissolve them in chloroform to prepare a solution with a total concentration of 14 mg / mL (the mass ratio of LJQD-1 to Y6 is 1:1.2), and prepare a thin film on a quartz substrate by spin coating (single spin coating solution volume 15 μL, spin coating speed 3000 Rpm).
[0090] Among them, the structure of Y6 is as follows Figure 6 shown.
[0091] Figure 5 Figure 3 is the UV-visible light (UV) absorbance curve of LJQD-1 solid film, Y6 solid film and LJQD-1:Y6 mixed film. It can be seen that the absorption of polymer LJQD-1 solid film is mainly concentrated in the range of 300-650nm, while the absorption of Y6 solid film is mainly concentrated in the range of 650-800nm. The absorption of light by LJQD-1 just makes up for the lack of Y6 absorption range. The mixed film of the two (LJQD-1:Y6 mixed film) has good absorption capacity in the visible light range. Therefore, LJQD-1 is suitable as a donor material for solar cells.
[0092] Test Example 2
[0093] The polymer LJQD-1 synthesized in Example 2 was used as the photovoltaic active layer of the organic solar cell, and the performance test was carried out.
[0094] Organic solar cells (OSCs) device preparation
[0095] The structure of OSCs was prepared using the conventional structure of glass substrate (1 mm) / ITO cathode (100 nm) / PEDOT:PSS cathode interface layer (5 nm) / LJQD-1:Y6 photovoltaic active layer (100 nm) / PNDIT-F3N anode interface layer (20 nm) / Ag anode (100 nm);
[0096] in, Figure 8 The device structure diagram of organic solar cells (OSCs);
[0097] The detailed preparation process of the organic solar cell is as follows:
[0098] In a nitrogen atmosphere glove box, the sheet resistance was 20 Ω / cm 2The ITO conductive glass substrate was pre-cut into 15mm×15mm square pieces, and then cleaned with isopropanol, surfactant, deionized water, and isopropanol ultrasonically, and then placed in a constant temperature oven for use after drying. A 5nm thick layer of PEDOT:PSS was spin-coated on the ITO, and then LJQD-1:Y6 with a mass ratio of 1:1.2 was spin-coated as the photovoltaic active layer material, and then the anode interface layer PNDIT-F3N-Br was spin-coated, and finally the Ag electrode was evaporated;
[0099] The current-voltage curve of the prepared battery device is shown in Figure 7 As shown, the relevant data are listed in Table 1.
[0100] Table 1 Performance parameters of organic solar cells when LJQD-1 is used as electron donor material
[0101]
[0102] It can be seen that the conjugated polymer containing benzisoxazole described in the present invention can greatly increase the current of battery devices and improve battery efficiency, mainly by achieving a good balance between fill factor, short-circuit current and open-circuit voltage.
[0103] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0104] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A monomer material containing a benzisoxazole structure, characterized in that: The monomer material containing a benzisoxazole structure has the following structure: in, The R is selected from alkyl derivatives; Said A1 and A2 are independently selected from alkyl and alkyl derivatives; The B1 and B2 are independently selected from oxygen atoms and nitrogen atoms, and the types of the selected B1 and B2 are different.
2. The monomer material containing a benzisoxazole structure according to claim 1, characterized in that: All carbon atoms on the alkyl derivative are unsubstituted, or one or more carbon atoms are substituted by one or more of oxygen atoms, nitrogen atoms, phosphorus atoms, amino groups, sulfone groups, carbonyl groups, aryl groups, alkenyl groups, alkynyl groups, ester groups, cyano groups, and nitro groups; All hydrogen atoms on the alkyl derivative are unsubstituted, or one or more hydrogen atoms are substituted by one or more of halogen, hydroxyl, amino, carboxyl, cyano, nitro, aryl, alkene, and alkyne.
3. The method for preparing the monomer material containing benzisoxazole structure according to any one of claims 1 to 2, characterized in that: The steps include: L1, adding halogenated benzaldehyde to fuming nitric acid, nitrifying reaction, purifying, to obtain compound 2; L2, adding compound 2 to a solvent, adding a reducing agent under the protection of an inert gas, stirring to react, and purifying to obtain compound 3; L3. Under the protection of an inert gas, compound 3, a tributyltinated thiophene unit containing an R group, and a catalyst are added to a solvent, heated for reaction, and purified to obtain compound 4; L4, adding the compound 4 into a solvent, and then adding a halogenating agent, reacting, and purifying to obtain a monomer material containing a benzisoxazole structure.
4. The method for preparing a monomer material containing a benzisoxazole structure according to claim 3, characterized in that: In step L1, multiple hydrogen atoms in the halogenated benzaldehyde are replaced by halogen atoms; The halogen is selected from chlorine, bromine and iodine.
5. The method for preparing a monomer material containing a benzisoxazole structure according to claim 3, characterized in that: In step L2, the reducing agent is selected from one or more of stannous chloride, potassium borohydride, sodium borohydride, and lithium aluminum hydride.
6. A conjugated polymer composite material containing benzisoxazole, characterized in that: The conjugated polymer composite material containing benzisoxazole has the following structure: Wherein, n is a natural number greater than 1; The C unit is an electron donating group.
7. The conjugated polymer composite material containing benzimidazole according to claim 6, characterized in that: The C unit is selected from one or more of the following structures: Wherein, R1 and R2 are independently selected from alkyl and alkyl derivatives; One or more carbon atoms on the alkyl derivative are substituted by one or more of oxygen atoms, amino groups, sulfone groups, carbonyl groups, aryl groups, alkenyl groups, alkynyl groups, ester groups, cyano groups, and nitro groups; and / or One or more hydrogen groups on the alkyl derivative are replaced by one or more of halogen, hydroxyl, amino, carboxyl, cyano, nitro, aryl, alkene, and alkyne.
8. The method for preparing the conjugated polymer composite material containing benzisoxazole according to any one of claims 6 to 7, characterized in that: The steps include: The monomer material containing the benzisoxazole structure, the coupling compound and the catalyst are added into the solvent, heated for reaction under the protection of an inert gas, and purified to obtain the conjugated polymer composite material containing the benzisoxazole.
9. The method for preparing the conjugated polymer composite material containing benzisoxazole according to claim 8, characterized in that: The coupling compound is selected from one of a bis(trimethyltin) terminal compound and a bis(borate) terminal compound.
10. Use of the conjugated polymer composite material containing benzisoxazole according to any one of claims 6 to 7 in plastic modification.